The effect of blood glucose, blood lactate and creatine kinase levels after carbohydrate-protein supplement uptake on recovery period after exercise in pencak silat athletes - Boonhan, Preeyapat (STKIP PGRI Jombang, 2023)
Pencak Silat, a traditional martial art from Southeast Asia, has gained recent popularity, prompting interest in performance enhancement methods. Therefore, The purpose of this study is to examine the effects of carbohydrate-protein supplementation on blood glucose, blood lactate, and creatine kinase levels at the period of recovery after exercise in Pencak Silat Athletes. Materials and Methods: Thirty elite athletes (average age 18-25 years) participated, divided into three groups, each undergoing a 90-minute cycling session at 75% VO₂ max. Participants consumed CHO-PROT, carbohydrate (CHO), or placebo (PLA) drinks 15 minutes before and 45 minutes after exercise. Blood samples were collected before, during, and after exercise. Results: indicated that CHO-PROT and CHO groups exhibited significantly higher blood glucose levels compared to the PLA group (p<0.05), particularly around 75 minutes and 1.5 hours post-exercise. Blood lactate levels did not significantly differ among groups post-exercise. Notably, CHO-PROT consumption led to lower creatine kinase levels compared to CHO and PLA groups (p<0.05), suggesting reduced muscle damage. CHO consumption also demonstrated lower creatine kinase levels compared to the PLA group (p<0.05). Conclusions: CHO-PROT supplementation can elevate blood glucose during post-exercise recovery without influencing blood lactate, highlighting its potential benefits for Pencak Silat athletes.